COVID-19 vaccine induced Guillain-Barre syndrome: a case report - Shamim, M.; Nawaz, Ghulam; Sinha, Rani Indira (International Journal of Basic & Clinical Pharmacology, 2022)
Guillain-Barre syndrome (GBS) is a rare immune mediated clinical disorder of the peripheral nerves. A number of vaccines including COVID-19 vaccine have been shown to be associated with an increased risk of GBS. We reported a case of Corbevax® (COVID-19 vaccine) induced GBS. A 12 years old girl presented to the paediatric emergency with 2 days history of progressive weakness of all four limbs. The weakness started after one day of patient received her first dose of Corbevax®. Neurological examination findings were weakness, decreased muscles tone, decreased muscles power, diminished or absent deep tendon reflexes of all four limbs. The findings of cerebrospinal fluid showed increase in protein and normal cell count. The diagnosis of GBS was confirmed by nerve conduction studies. After confirmation of the diagnosis, she was given intravenous immunoglobulin (IVIG) with the dose of 2 g/kg body weight divided over 5 consecutive days. Then the patient was examined, clinical condition was improved dramatically. GBS rarely caused by COVID-19 vaccination. GBS may become life threatening due to respiratory muscles involvement. In about 30% of cases may require admission in Intensive Care Unit and need for mechanical ventilatory support. So careful monitoring is required after administration of COVID-19 vaccine. This case report never discourages the vaccine rollout, but monitoring of evolving data should be carried on by manufacturers and independent authorities coming to a definite conclusion.